One world is not enough: the structured phenomenology of lifestyle migrants in East Asia. (25th February 2018) - Stones, Rob; Botterill, Kate; Lee, Maggy; O'Reilly, Karen
Abstract: The paper is based on original empirical research into the lifestyle migration of European migrants, primarily British, to Thailand and Malaysia, and of Hong Kong Chinese migrants to Mainland China. We combine strong structuration theory (SST) with Heideggerian phenomenology to develop a distinctive approach to the interplay between social structures and the lived experience of migrants. The approach enables a rich engagement with the subjectivities of migrants, an engagement that is powerfully enhanced by close attention to how these inner lives are deeply interwoven with relevant structural contexts. The approach is presented as one that could be fruitfully adopted to explore parallel issues within all types of migration. As is intrinsic to lifestyle migration, commitment to a better quality of life is central to the East Asian migrants, but they seek an uncomplicated, physically enhanced texture of life, framed more by a phenomenology of prosaic well‐being than of self‐realization or transcendence. In spite of possessing economic and status privileges due to their relatively elite position within global structures the reality for a good number of the lifestyle migrants falls short of their prior expectations. They are subject to particular kinds of socio‐structural marginaliszation as a consequence of the character of their migration, and they find themselves relatively isolated and facing a distinct range of challenges. A comparison with research into various groups of migrants to the USA brings into relief the specificities of the socio‐structural positioning of the lifestyle migrants of the study. Those East Asian migrants who express the greatest sense of ease and contentment seem to be those who have responded creatively to the specific challenges of their socio‐structural situation. Often, this appears to have been achieved through understated but active involvements with their new settings and through sustaining focused transnational connections and relationships.